A biopsychosocial vignette for case conceptualization in dementia (VIG-Dem): development and pilot study. (7th April 2016) - Spector, Aimee; Hebditch, Molly; Stoner, Charlotte R.; Gibbor, Luke
ABSTRACT: Background: The ability to identify biological, social, and psychological issues for people with dementia is an important skill for healthcare professionals. Therefore, valid and reliable measures are needed to assess this ability. This study involves the development of a vignette style measure to capture the extent to which health professionals use "Biopsychosocial" thinking in dementia care (VIG-Dem), based on the framework of the model developed by Spector and Orrell (2010 ). Methods: The development process consisted of Phase 1: Developing and refining the vignettes; Phase 2: Field testing ( N = 9), and Phase 3: A pilot study to assess reliability and validity ( N = 131). Results: The VIG-Dem, consisting of two vignettes with open-ended questions and a standardized scoring scheme, was developed. Evidence for the good inter-rater reliability, convergent validity, and test–retest reliability were established. Conclusions: The VIG-Dem has good psychometric properties and may provide a useful tool in dementia care research and practice.